Can a for loop increment/decrement by more than one?

Can a for loop increment/decrement by more than one?

Are there other ways to increment a for loop in Javascript besides i++ and ++i? For example, I want to increment by 3 instead of one.
for (var i = 0; i < myVar.length; i+3) { //every three }

Solutions/Answers:

Solution 1:

Use the += assignment operator:

for (var i = 0; i < myVar.length; i += 3) {

Technically, you can place any expression you’d like in the final expression of the for loop, but it is typically used to update the counter variable.

For more information about each step of the for loop, check out the MDN article.

Solution 2:

A for loop:

for(INIT; TEST; ADVANCE) {
    BODY
}

Means the following:

INIT;
while (true) {
    if (!TEST)
        break;
    BODY;
    ADVANCE;
}

You can write almost any expression for INIT, TEST, ADVANCE, and BODY.

Do note that the ++ operators and variants are operators with side-effects (one should try to avoid them if you are not using them like i+=1 and the like):

  • ++i means i+=1; return i
  • i++ means oldI=i; i+=1; return oldI

Example:

> i=0
> [i++, i, ++i, i, i--, i, --i, i]
[0, 1, 2, 2, 2, 1, 0, 0]

Solution 3:

for (var i = 0; i < 10; i = i + 2) {
    // code here
}​

Solution 4:

Andrew Whitaker’s answer is true, but you can use any expression for any part.
Just remember the second (middle) expression should evaluate so it can be compared to a boolean true or false.

When I use a for loop, I think of it as

for (var i = 0; i < 10; ++i) {
    /* expression */
}

as being

var i = 0;
while( i < 10 ) {
    /* expression */
    ++i;
}

Solution 5:

You certainly can. Others have pointed out correctly that you need to do i += 3. You can’t do what you have posted because all you are doing here is adding i + 3 but never assigning the result back to i. i++ is just a shorthand for i = i + 1, similarly i +=3 is a shorthand for i = i + 3.

Solution 6:

for (var i = 0; i < myVar.length; i+=3) {
   //every three
}

additional

Operator   Example    Same As
  ++       X ++        x = x + 1
  --       X --        x = x - 1
  +=       x += y      x = x + y
  -=       x -= y      x = x - y
  *=       x *= y      x = x * y
  /=       x /= y      x = x / y
  %=       x %= y      x = x % y